2022
DOI: 10.3389/fpsyg.2022.861447
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Proactive Personality and Entrepreneurial Intentions in College Students: Mediation Effects of Social Capital and Human Capital

Abstract: The research aims to explore the influence mechanism of proactive personality on the entrepreneurial intentions of college students. Adopting proactive personality scale, social capital scale, human capital scale, and entrepreneurial intention scale, this research tested valid samples of 300 Chinese college students. The results revealed that proactive personality exerted a significant and positive impact on the entrepreneurial intentions. Social capital played a partial mediating role between the proactive pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 84 publications
2
13
0
1
Order By: Relevance
“…In addition, when examining entrepreneurial intentions among college students, several studies have shown the following results: significant and positive effects of encouragement and support from family members, relatives, and friends ( Davidsson and Honig, 2003 ; Baughn et al, 2006 ); practical entrepreneurship education organization can positively affect the entrepreneurship learning process and increase entrepreneurship alertness and intention ( Kuckertz, 2013 ); Luo et al (2022) revealed that social relations can significantly impact and promote the entrepreneurial intention of college students; practical entrepreneurial learning helps students acquire relevant entrepreneurship experience, which both increases their understanding of the theory–reality gap and ability to identify entrepreneurial opportunities, thereby improving entrepreneurial intention ( Ramsgaard and Østergaard, 2018 ).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…In addition, when examining entrepreneurial intentions among college students, several studies have shown the following results: significant and positive effects of encouragement and support from family members, relatives, and friends ( Davidsson and Honig, 2003 ; Baughn et al, 2006 ); practical entrepreneurship education organization can positively affect the entrepreneurship learning process and increase entrepreneurship alertness and intention ( Kuckertz, 2013 ); Luo et al (2022) revealed that social relations can significantly impact and promote the entrepreneurial intention of college students; practical entrepreneurial learning helps students acquire relevant entrepreneurship experience, which both increases their understanding of the theory–reality gap and ability to identify entrepreneurial opportunities, thereby improving entrepreneurial intention ( Ramsgaard and Østergaard, 2018 ).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Furthermore, a stable social environment enhances the possibility that individuals would leave their occupations and pursue entrepreneurship prospects, which is why new entrepreneurs typically start new enterprises in the same location where they have lived for a long time [24][25][26]. Several empirical studies demonstrate a strong relationship between social capital and EI [2,9,25]. Based on the above argument, the study presents the following hypothesis: H1: Social capital will have a significant positive effect on polytechnic students' EI.…”
Section: Social Capital and Entrepreneurial Intentionmentioning
confidence: 99%
“…Scholars have been primarily interested in investigating the construct of entrepreneurial intention (EI, hereafter) over the last several decades [5] as it is the most important predictor of new firm formation [5][6][7]. Recently, research has focused on the importance of social capital in entrepreneurship [8,9]. Social capital fosters entrepreneurship by giving individuals resources from family members, friends, the community, and society [8,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations